Valdosta High School Scrapbook 29, May 1979 – December 1979 - Valdosta High School (My University, 1979)
This item is a collection of newspaper clippings with photographs. The item primarily focuses on the football season for Valdosta High School. There are some reports about the scores from the games played by Valdosta including Thomasville and Lowndes County. Other sports like Basketball and baseball are mentioned but they are not the primary focus.
This item contains 1 PDF file with 95 pages and a title page. Additionally there are 63 JPG files
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.); American Football